On the capacity and security of steganography approaches: an overview - Hmood, A.K.; Jalab, H.A.; Kasirun, Z.M.; Zaidan, A.A.; Zaidan, B.B. (2010)
The aim of this study is to review the strength and weakness for the possible multimedia cover for the steganography approaches. In addition, the security level of each approach and how is probable to combine the steganography and cryptography. Steganography is an art on which the data can be hide in other data as cover, the multimedia files is the commonly used for hiding data. The main aspects of the steganography is the capacity and security, where the capacity refer to how much data can be hidden in the cover carrier, while the security concern with the ability of disclose or altering the data by unauthorized party. The multimedia files, such as, image, video, audio and text are the possible covers for hiding secure information or data. Each of these covers has advantages and disadvantages; as a result of this study we will discuss the possibility to use these files as a cover. In the last part of this study, we suggest a further direction to improve the capacity and security aspects.